Rainy day - The Corrs; Sasha; WARNER Music (Malaysia). (Kuala Lumpur : Warner Music, 1998)
Contains the single from'The Corrs Unplugged' album and the single by another performer taken from'Dedicated To...' album.
Rainy Day / The Corrs -- I Feel Lonely / Sasha.
Koleksi Khas Wiramanja.
Title from disc label.